Morphological variation in two genetically distinct groups of the golden-striped salamander, Chioglossa lusitanica (Amphibia: Urodela) - Alexandrino, João [UNESP]; Ferrand, N.; Arntzen, J. W. (Brill Academic Publishers, 2006)
Morphometric and colour pattern variation in the endemic Iberian salamander Chioglossa lusitanica is concordant with the genetic differentiation of two groups of populations separated by the Mondego river in Portugal. Salamanders from the south have shorter digits than those from the north. Clinal variation with a south to north increase in limb, toe and finger length was found superimposed on this dichotomy, resulting in stepped clines for characters describing appendage size. Genetic variability was paralleled by colour pattern variability in the contact zone and in northern populations. To explain the observed parallels we invoke the neutral processes of vicariant isolation, admixture in a secondary contact zone, genetic drift in addition to selection acting along an environmental gradient. Morphological constraints imposed by a highly specialized ecological niche may explain why the genetic subdivision of C. lusitanica since the early Pleistocene has remained fairly cryptic.
Keywords: Amphibia; Chioglossa lusitanica; Clinal variation; Colour pattern; Golden-striped salamander; Morphometrics